Flipped Learning for Elementary Instruction - Sams, Aaron (Book collections on Project MUSE., 2016)
Building on their best-selling book Flip Your Classroom: Reach Every Student in Every Class Every Day, flipped education innovators Jonathan Bergmann and Aaron Sams return with a book series that supports flipped learning in the four topic areas of science, math, English and social studies as well as the elementary classroom. In this volume the authors address how flipping your classroom can support elementary instruction.